Optimum Conditions for Frying Cavendish Bananas by Vacuum Fryer - Khongsit, Phensiri; Salungyoo, Kanya; Sangchaiyapoom, Saiparn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2023)
This research aimed to study the optimal conditions for frying cavendish banana by vacuum fryer. Two main factors were studied: oil temperature (75, 80, and 85 ºC) and frying time (50, 60, and 70 min). The frying was done under vacuum pressure of 84 kPa with a centrifugation speed of 900 rpm for 15 minutes to eliminate oils on the surface. Cavendish bananas with maturity index 5 (yellow peel throughout the fruit) were washed, peeled and sliced to a thickness of 0.5 cm, and followed by soaking in 0.02 % sodium metabisulfite solution for 1 min and 0.5 % CaCl solution for 1 min. The results showed that frying cavendish banana at oil temperature 75 ºC for 70 min produced the best product in terms of texture and sensory evaluation. The different frying temperatures and times significantly affected the quality of the product (p≤0.05). The product had moisture content of 0.26 %. L*, a* and b* values were 47.88, 7.29, and 30.89, respectively, while hardness was 5.21 kg, and crispiness was 16.88 kg/s. The chemical component including moisture, fat, protein, fiber, ash, carbohydrate and total energy were 1.60 %, 20.63, 1.155, 5.31, 1.33 %, 69.98 % and 470.26 kcal, respectively. The peroxide value was 0.79 mg/kg and microbiological quality did not exceed the standard requirements.